Validity of decision support systems: towards a validation methodology. - Finlay, Paul N.; Wilson, John M. (Systems Research & Behavioral Science)
The writers aim to nurture a debate within the modeling community as to the most appropriate validation methodology to apply in cases when validation is carried out by nonspecialists, which is occurring as a result of the widespread use in business of information systems based on mathematical models developed by end users. The writers concentrate on lone-user decision support systems (DSS). In reviewing methodologies for validation, they suggest a simple, operationalizable validity framework that is usable by both systems builders and by users. They present an example of the use of the framework with a simple DSS using a spreadsheet, which is the most common form of DSS. They state that this framework is intended to offer the basis for the development of a practical validation methodology, one that is contingent on the context in which the system will be constructed and applied.